Delinquency in Informal Youth Groups - Gavėnaitė, Aušra (Sociologija. Mintis ir veiksmas, 2003)
This paper presents empirical research about delinquency in informal youth groups in Lithuania. The theoretical basis of this research - theory of delinquency and drift, created in the midst of the XX th century by David Matza - famous USA criminologist, whose efforts to combine positivist point of view with classical ideas gave way to a new - critical School of criminology. Empirical research was carried out in three youth groups: football fans group “ultra”, nationalistic group - skinheads and motorbike club - “Vorai”. The main tasks of this research were to identify, what kind - “delinquent subculture” or “subculture of delinquency” - these groups are and to explore the process of drifting from conventional to delinquent behavior by using techniques of neutralization. The results show, that these groups are an integral part of conventional society and have no features of “delinquent subculture” as it was depicted in positivistic theories. The members of the groups are normal teenagers, who by definition (but not by nature) are delinquents as far as they do infractions. To make an infraction these teens use different techniques of neutralization.
Keywords: delinquency; delinquent; delinquent subculture; neutralization; infraction